PENGARUH BANTUAN KREDIT PERBANKAN TERHADAP PERKEMBANGAN UMKM (STUDI KASUS UMKM DI KOTA PONTIANAK) - Udin Rinaldi; Ana Yuliana (Jurnal Ekonomi Integra, 2022)
The research objective is to analyze the development of bank credit towards the development of Micro, Small and Medium Enterprises (MSME) case studies in Pontianak City. Explanatory research aimed at discussing hypotheses and in accordance with research objectives. Provision of bank credit in this case is commercial bank credit consisting of Bank Mandiri, Bank BRI and Bank BPD Kalbar. Population of 415 MSME units that received credit assistance were then sampled as many as 75 respondents who needed at least one year of assistance. The regression used in explaining the effect of giving on the development of MSME businesses is needed through sales volume, labor force, total production and total assets. Lending by banks to MSMEs uses low interest earning productive credit schemes. The results of the study explain that lending influences business development significantly, which affects the sales volume of MSMEs, significantly influences the application of labor, significantly influences the amount of production, and significantly influences the amount of assets.